Use of Geographic Information Systems to Analyze the Distribution of Water Catchment Areas in Ambon City, Indonesia - Rakuasa, Heinrich (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Ambon City, as the capital of Maluku province, faces serious challenges in water resources management due to rapid urbanization and climate change that affects rainfall patterns. This study aims to analyze the distribution of water catchment areas using Geographic Information Systems. Methods: This study used variables of rainfall, soil type, land use, and slope which were analyzed using Geographic Information System (GIS) approach with overlay technique. Findings: The results showed that the water catchment area in Ambon City with a rather critical condition has an area of 2,350.27 ha, good condition of 13,524.39 ha, starting critical condition of 2,827.62 ha, normal natural condition of 13,636.20 ha and very critical condition of 236.12 ha. This research shows that soil characteristics, land use, slope, and rainfall in Ambon City have a significant influence on the capacity of water catchment areas. Findings from analysis using Geographic Information Systems (GIS) show that soil type, land use, and slope have a significant effect on water infiltration capacity, with alluvial soils having the best infiltration capacity. Conclusion: The results of this study emphasize the need for better management and strict implementation of spatial policies to protect water catchment areas, in order to reduce disaster risk and support sustainable development in Ambon City.